Music as an intervention in health projects - Donda, Darlene Cristina; Leão, Eliseth Ribeiro (Revista da Escola de Enfermagem da USP, 2021)
Objective: To identify and characterize music projects in the health area, their therapeutic goals, theoretical frameworks, evaluation/monitoring, and dissemination of their results for a possible structure model for this process. Method: Descriptive study with multiple cases and documental analysis. Results: Nine projects have participated in this study; these were predominantly in São Paulo and conducted with the adult population in public institutions. The coordinators were mostly women, specialists, with a qualification in health, music, or both. The interventions were performed live, with a mean of 60 minutes per week and repertoires selected by patients. Less than half indicated basing their activities in some theoretical framework or any type of project monitoring. Therapeutic goals related to social insertion and restoring self-esteem, citizenship, protagonism, and communication were pointed out. Conclusion: The theoretical indication of the music projects was scarce. Around half the analyzed projects indicated some type of evaluation and dissemination of the performed activities. Two projects only had some risk surveillance and scientific production out of their results, which has not enabled proposing a monitoring model for these initiatives.